2022
DOI: 10.1038/s41467-022-32418-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient separation of butane isomers via ZIF-8 slurry on laboratory- and pilot-scale

Abstract: Abstractn-butane and isobutane are important petrochemical raw materials. Their separation is challenging because of their similar properties, including boiling point. Here, we report a zeolitic imidazolate framework-8 (ZIF-8)/N,N-Dimethylpropyleneurea (DMPU)-water slurry as sorption material to separate butane mixtures. The isobutane/n-butane selectivity of ZIF-8/DMPU-water slurries is as high as 890 with high kinetic performance, which transcends the upper limit of various separation materials or membranes r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In addition, Liu et al have conducted extensive studies on the optimization of process flow using current PL systems. 51 For instance, they created a hybrid technique for carbon capture by utilizing a ZIF-8 floating in liquid glycol (Figure 7d). The higher separation performance in type III PLs is due to the formation of semipermeable films when suitably porous ZIF materials are suspended in different HB-forming solvents.…”
Section: Gas Capturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Liu et al have conducted extensive studies on the optimization of process flow using current PL systems. 51 For instance, they created a hybrid technique for carbon capture by utilizing a ZIF-8 floating in liquid glycol (Figure 7d). The higher separation performance in type III PLs is due to the formation of semipermeable films when suitably porous ZIF materials are suspended in different HB-forming solvents.…”
Section: Gas Capturementioning
confidence: 99%
“…Toward this end, we have created PLs using PDMS as the sterically hindered solvent for CO 2 selective sorption (Figure c). In addition, Liu et al have conducted extensive studies on the optimization of process flow using current PL systems . For instance, they created a hybrid technique for carbon capture by utilizing a ZIF-8 floating in liquid glycol (Figure d).…”
Section: Porous Liquids Toward Task-specific Applicationsmentioning
confidence: 99%
“…With the advent of membrane-based separation technology, bulk microporous materials such as zeolites of crystalline aluminosilicates and activated carbon have been considered as promising alternatives. To date, zeolitic imidazolate framework (ZIF) membranes have presented advantages in separating CO 2 /H 2 , ethanol/water, p / o -xylene, , and n -butane/isobutane. , In addition, metal–organic frameworks (MOFs) with uniform pore distribution are a class of molecular sieve materials, whose diverse applications have also been reported. Wang et al investigated the separation performance of a series of Zr-based MOFs and concluded that Zr 6 O 4 (OH) 4 (bptc) 3 could adsorb n -hexane but exclude branched isomers in a C 6 alkenes mixture . Li et al found that due to multiple adsorption sites, MOF-303­(Al) could separate CO 2 from CO 2 /CH 4 and CO 2 /N 2 mixtures with high CO 2 capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Among solid sorbents used for Type 3 PLs, MOFs offer a unique opportunity to study the structure–property relationship between adsorption and porosity due to the ease of tunability of the porous frameworks. For example, MOFs can be judicially designed to tune the desired properties such as pore size, ligand functionality, and metal center. , Additionally, the surface of MOFs can be readily functionalized, allowing improved dispersion within liquids. ZIF–8 is a MOF from the zeolitic imidazole framework (ZIF) family that has recently shown promise for use in Type 3 PLs. This is due to the high hydrophobicity of the framework, which excludes water from the pores except under high hydrostatic pressures . As a result, ZIF–8 and related surface-functionalized versions have been shown to improve the uptake of gases, including CO 2 and O 2 , in both water and water–organic solvent mixtures. , However, aqueous ZIF-based PLs are not without other challenges. The formation of carbonates from the reaction of CO 2 with the solvent system can lead to framework degradation over time …”
Section: Introductionmentioning
confidence: 99%